Changes in propofol anaesthesia and dichlorvos toxicity in mice following repeated dosing with three hypolipidemic statins - R. F. Al-Shalchi; F. K. Mohammad (Bulgarian Journal of Veterinary Medicine)
Undesirable effects of hypolipidemic statins in rodents are characterised by neurobehavioural altera-tions with changes in the cholinergic/cholinesterase and neurotropic systems. The purpose of the study was to administer repeatedly three different statins: atorvastatin, simvastatin and rosuvastatin, in male Swiss mice and explore their behavioural outcomes after challenging them with the anaesthetic propofol and the cholinesterase inhibitor dichlorvos. A total of 92 mice were randomly allocated to each statin (200 mg/kg/day) or distilled water-control (10 mL/kg/day) treatment groups (n= 8 or 10 mice/group)for 28 consecutive days. Twenty-four hours after last statin or control dosing, mice were subjected to a pharmacological challenge with propofol at 100 mg/kg, intraperitoneally or to a toxico-logical challenge with dichlorvos at 150 mg active ingredient/10 mL distilled water/kg, orally. Propo-fol anaesthesia and dichlorvos-induced cholinergic toxidrome were separately monitored. Brain cholinesterase activity was also determined in statin-treated mice. Statins significantly decreased the latency to onset of propofol sleep and reduced the sleep duration. Following the toxicological chal-lenge, statins significantly increased the latency to onset of signs of poisoning and delayed the latency to onset of death within 4 h after the dichlorvos dosing. Statin treatments variably decreased signs of poisoning and death (37.5%87.5%) vs. control group (62.5%100%). Atorvastatin, simvastatin and rosuvastatin also significantly decreased dichlorvos toxicity score by 42%, 33% and 21%, and signifi-cantly reduced whole brain ChE activity by 54%, 42% and 42%, respectively. The results support values of pharmacological and toxicological challenges in mice to uncover changes in responses to propofol anaesthesia and dichlorvos intoxication following repeated statin treatments. Further studies are needed to explore neurochemical bases of statin effects.